S-Nitrosoglutathione Reductase Contributes to Thermotolerance by Modulating High Temperature-Induced Apoplastic H2O2 in Solanum lycopersicum - Song, Xuewei; Wang, Ting; Zhang, Yang; Yu, Jing-Quan; Xia, Xiao-Jian (Frontiers in Plant Science, 2022)
S-nitrosoglutathione reductase (GSNOR) is considered as a critical regulator of plant stress tolerance for its impacts on protein S-nitrosylation through regulation of the S-nitrosothiol (SNO) level. However, the mechanism of GSNOR-mediated stress tolerance is still obscure. Here, we found that GSNOR activity was induced by high temperature in tomato (Solanum lycopersicum) plants, whereas mRNA level of SlGSNOR1 exhibited little response. Suppressing SlGSNOR1 expression by virus-induced gene silencing increased accumulation of SNO and nitric oxide under high temperature and reduced thermotolerance. The compromised thermotolerance was associated with less accumulation of abscisic acid and salicylic acid, attenuated activation of mitogen-activated protein kinase and reduced expression of heat shock protein. Intriguingly, SlGSNOR1 silencing impaired upregulation of RESPIRATORY BURST OXIDASE HOMOLOG1 (SlRBOH1) and apoplastic H2O2 accumulation in response to high temperature, whereas SlRBOH1 silencing abolished activation of GSNOR and led to a similar decline in thermotolerance as in SlGSNOR1-silenced plants. Importantly, H2O2 treatment recovered the thermotolerance and improved antioxidant capacity in SlGSNOR1-silenced plants. Our results suggest that GSNOR plays a role in regulating the SlRBOH1-dependent apoplastic H2O2 production in response to high temperature, while a balanced interaction between SNO and H2O2 is critical for maintaining the cellular redox homeostasis and thermotolerance.